The Relationship Between Accountability, Transparency, Human Resource Competence, Information Technology Utilization, and Organizational Commitment to the Quality of Local Government Financial Reports in Tanjung Jabung Barat Regency - Risty Bewinda Aferanti; Afrizal; Fredy Olimsar (Greenation International Journal of Economics and Accounting, 2025)
The purpose of this study is to analyze the relationship between accountability, transparency, human resource competence, information technology implementation, and organizational commitment on the one hand, and the quality of financial reports published by the West Tanjung Jabung Regency Government on the other. Adopting a quantitative methodology, this study used a survey approach by distributing questionnaires to 131 employees in the financial units of the Regional Apparatus Organization (OPD) in Tanjung Jabung Barat Regency. Multiple correlation analysis was performed using SPSS Version 27 for Windows software. The findings show that, collectively, accountability, transparency, human resource competence, information technology implementation, and organizational commitment have a significant relationship with the quality of financial reports. Individually, each of these five independent variables also has a positive and significant effect on the quality of financial reports. The Adjusted R Square value of 44.7% indicates that these variables explain 44.7% of the variability in financial report quality, with the remainder being caused by other factors.